Nurses Barrier: A Patient Safety Concern in The Intensive Care Unit - Gunawan Gunawan; Hanik Endang Nihayati; Listianingtri Puspitasari; Muhammad Ali Machrus (Palembang MediRose Publisher, 2022)
Patient safety became one of the most important indicators in maintaining the quality of nursing service in the hospital. Patient, individual staff, team, task and technology, work environment, organizational and management, and institutional context factors are all examples of obstacles nurses encounter when attempting to ensure patient safety in the hospital setting. Lastly, nurses should put concern in patient safety to make sure the quality by considering the behaviour and refer to Laurence Green Theory.